Antimicrobial activity and productivity of γ-aminobutyric acid in lactic acid bacteria isolated from traditional Gifu ayu-narezushi - Hori, Mitsuyo; Kawai, Yusuke; Noguchi, Koichiro; Nakamura, Kohei; Shimada, Masaya; Iwahashi, Hitoshi; Nakagawa, Tomoyuki (Food Science and Technology Research, 2024)
From traditional Gifu ayu-narezushi, Leuconostoc, Latilactobacillus, and Enterococcus were isolated as dominant genera. Isolated strains of Leuconostoc mesenteroides showed high growth inhibition activity against Staphylococcus aureus and Escherichia coli. The isolated strain, Enterococcus lactis EC52, could produce γ-aminobutyric acid (GABA). These results indicated that Enterococcus lactis and Leuconostoc mesenteroides were lactic acid bacteria, which have GABA-producing and antimicrobial activities, respectively, in traditional Gifu ayu-narezushi.